1989–1991. Диагноз времени - Попова, И. (Социология: теория, методы, маркетинг, 2004)
The 1989–1991 called the “crisis of Perestroika” can be characterized by various chances and development options. The article presents an analysis of these chances and explains why the post-soviet transformation lead to the “confrontation and criminal” option.